2021
DOI: 10.3390/s21217038
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Jaundice Diagnosis Using a Smartphone Camera Based on Eye, Skin, and Fused Features with Transfer Learning

Abstract: Neonatal jaundice is a common condition worldwide. Failure of timely diagnosis and treatment can lead to death or brain injury. Current diagnostic approaches include a painful and time-consuming invasive blood test and non-invasive tests using costly transcutaneous bilirubinometers. Since periodic monitoring is crucial, multiple efforts have been made to develop non-invasive diagnostic tools using a smartphone camera. However, existing works rely either on skin or eye images using statistical or traditional ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Another study in China demonstrated decreased neonatal readmission rate and decreased maternal anxiety scores for mother-infant dyads that used a smartphone app to monitor for neonatal jaundice at home under web-based guidance of pediatricians compared to the control group that received routine care ( 108 ). Similar smartphone-based detection tools are being studied in other regions of the world, including Singapore ( 109 ), Ghana ( 110 ), and Saudi Arabia ( 111 ), and Nigeria ( 112 ), just to name a few. Although these tools are best suited as screening devices, as with the TcB, they are encouraging uses of state-of-the-art technology to improve the recognition and diagnosis of NJ.…”
Section: Opportunities For Future Stepsmentioning
confidence: 99%
“…Another study in China demonstrated decreased neonatal readmission rate and decreased maternal anxiety scores for mother-infant dyads that used a smartphone app to monitor for neonatal jaundice at home under web-based guidance of pediatricians compared to the control group that received routine care ( 108 ). Similar smartphone-based detection tools are being studied in other regions of the world, including Singapore ( 109 ), Ghana ( 110 ), and Saudi Arabia ( 111 ), and Nigeria ( 112 ), just to name a few. Although these tools are best suited as screening devices, as with the TcB, they are encouraging uses of state-of-the-art technology to improve the recognition and diagnosis of NJ.…”
Section: Opportunities For Future Stepsmentioning
confidence: 99%
“…Althnian et al [25] propose a thorough exchange learning technique based on eye, skin, and merged images. In addition, they created conventional machine learning models, such as multi-layer perceptron (MLP), decision tree (DT), support vector machine (SVM), and random forest (RF), and compared their performance to that of the exchange learning signal.…”
Section: An Overview Of the Various Non-invasive Techniques Used For ...mentioning
confidence: 99%
“…Smartphone-based applications [17][18][19][20][21][22][23][24][25][26][27] that estimate the severity of jaundice raise the possibility of remote monitoring of neonatal jaundice (see Table 1). The 'Biliscan (Shenzhen Beishen Healthcare Technology Co, Shen Zhen, People's Republic of China)' is one such application.…”
Section: What This Paper Addsmentioning
confidence: 99%